Économie de la Rome antique. Histoire et historiographie. Recueil d'articles de Jean Andreau - Andreau, Jean (PrimaLun@, 2021)
This collection brings together thirty-three articles by Jean Andreau, all of which have already been published elsewhere, in journals or collective works. The oldest date from the 1970s and the most recent from the 2010s. Some of them deal with the work of the great Russian historian of the ancient economy, Michel I. Rostovtzeff. The others deal with some of the major aspects of the economic and social life of the ancient Roman world: currency and markets; the economic and financial policy of the Empire; the economic interests of the elites; the milieu of the former slaves, the freedmen, who played a major role in manufacturing and trade; and finally, social relations and social mobility.